2002
DOI: 10.1063/1.1516236
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation and linewidth enhancement factor in InGaAs quantum dot lasers

Abstract: Articles you may be interested inObservations of near-zero linewidth enhancement factor in a quantum-well coupled quantum-dot laser High-gain coupled InGaAs quantum well InAs quantum dot AlGaAs-GaAs-InGaAs-InAs heterostructure diode laser operation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 10 publications
1
39
0
Order By: Relevance
“…The threshold value of ρ for which there exists one eigenvalue λ k with ℜ(λ k ) > 0 is smaller for α positive than for α negative. This is consistent with the experimental observation that the filamentation threshold is higher in quantum dots than in bulk semiconductor lasers [18]. As a consequence, the range of control parameters where non-normal effects can be observed is larger for α < 0 than for α > 0.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The threshold value of ρ for which there exists one eigenvalue λ k with ℜ(λ k ) > 0 is smaller for α positive than for α negative. This is consistent with the experimental observation that the filamentation threshold is higher in quantum dots than in bulk semiconductor lasers [18]. As a consequence, the range of control parameters where non-normal effects can be observed is larger for α < 0 than for α > 0.…”
supporting
confidence: 91%
“…The parameter α is the line-enhancement factor: it is proportional to the ratio of the derivatives of the refractive index and of the gain with respect to the population and is different from zero if the gain line is asymmetric. The α factor is positive in bulk semiconductor lasers and quantum well lasers; it can be negative in quantum dot lasers [17,18] and in Raman lasers [19]. Here we consider for illustration purposes the values a = 0.01, b = 0.8, c = 0 and σ = 0.1 that are used in [12].…”
mentioning
confidence: 99%
“…Furthermore, for highly localized QD states, the absorption coefficient at the photon energies ϳ0.8 -1.0 eV due to these transitions can be on the order of 10 3 Carrier-induced refractive index changes can strongly influence characteristics of semiconductor laser and amplifiers, such as spectral linewidth, wavelength chirping, mode competition, and beam filamentation. [1][2][3][4][5] In bulk and quantum well ͑QW͒ devices, the index change includes an anomalous dispersion component res due to interband resonant transitions and a ''free carrier'' component free , originating from intraband transitions ͓see Fig. 1͑a͔͒:…”
mentioning
confidence: 99%
“…First theoretical and experimental investigations on the linewidth enhancement factor ͑␣-factor͒ have shown that the quantum-dot laser exhibits less filamentation than the quantum-well laser. 3 In this letter, we investigate the spatiotemporal dynamics and beam quality of InGaAs quantumdot lasers ͑dot density 10 11 cm Ϫ2 ) emitting at 1.1 m. For direct comparison with quantum-well lasers, we contrast and compare our theoretical and experimental results with corresponding lasers with a quantum-well gain medium, but identical waveguide structure.Our theoretical analysis is based on an effective multimode Maxwell-Bloch approach 4 that takes into account, in particular, the spatially and temporally varying material properties ͑of, e.g., the quantum-well or the active dot ensemble͒ and physical interactions that have a detrimental influence on beam quality and spectral characteristics. Simulations on the basis of this approach provide an interpretation of experimental results such as near-field profiles, power, and beam quality factor M 2 .…”
mentioning
confidence: 99%
“…First theoretical and experimental investigations on the linewidth enhancement factor ͑␣-factor͒ have shown that the quantum-dot laser exhibits less filamentation than the quantum-well laser. 3 In this letter, we investigate the spatiotemporal dynamics and beam quality of InGaAs quantumdot lasers ͑dot density 10 11 cm Ϫ2 ) emitting at 1.1 m. For direct comparison with quantum-well lasers, we contrast and compare our theoretical and experimental results with corresponding lasers with a quantum-well gain medium, but identical waveguide structure.…”
mentioning
confidence: 99%